The CUORE cryostat: commissioning and performance. Issue 6 (May 2016) - Singh, V; Alduino, C; Alessandria, F.; Bersani, A; Biassoni, M; Bucci, C; Caminata, A; Canonica, L; Cappelli, L; Cereseto, R; Chott, N; Copello, S; et al.
Abstract: The Cryogenic Underground Observatory for Rare Events (CUORE) will search for the 0 vββ decay in 130 Te using a cryogenic array of TeO2 bolometers, operated at a base temperature of 10mK. CUORE will consist of a closely packed array of 19 towers each containing 52 crystals, for a total mass of 741kg. The detector assembly is hosted in one of the largest cryostats ever constructed and will be cooled down to base temperature using a custom-built cryogen free dilution refrigerator. The CUORE cryostat along with the pulse tube based dilution refrigerator has been already commissioned at Laboratori Nazionali del Gran Sasso (LNGS) and a record base temperature, on a cubic meter scale, of 6mK was achieved during one of the integration runs. We present the results from integration runs, characterizing the system and the cooling performance of the dilution refrigerator, effectively showcasing its stability at base temperature for the expected thermal load.